Therapeutic Communication in the Development of Education in the Post-Modern Era - Maruli Tua Tampubolon (Riwayat: Educational Journal of History and Humanities, 2023)
The application of therapeutic communication concepts in education has garnered attention as a means to enhance the effectiveness of the learning process. This article examines the positive potentials of this approach, including increased student engagement, personalized learning, and the development of deeper relationships between teachers and students. However, challenges such as time constraints, large class sizes, and lack of training may impact optimal implementation. Through training, ongoing efforts, and support from school administrations, the application of therapeutic communication can be overcome, yielding positive impacts in the learning process.